PENGEMBAGAN MATERI PROSPEK KARIR DARI BERBAGAI PROGRAM STUDI DI PERGURUAN TINGGI SISWA KELAS XI IPA 3 SMA NEGERI 2 TAMBANG TAHUN AJARAN 2015/2016 - Perniawati '; Elni Yakub; Raja Arlizon (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : One of the efforts made in selected courses and career prospects was good and in accordance with the ability of self. That was the way to prepared and plan a career, found out information about the types of courses and career prospects inorder not to get confused in taking the decision to choose courses in college. Therefore, the researchers felt the needed to develop a material about the career prospects of the various courses of study at colleges that was expected to be used by teachers for guidance and counseling gave to students. This material was prepared used methods of research and development (R & D). The purpose of this research was 1) Establishment of career prospects material of various courses in college that was suitable for students of second grade class IPA 3 at SMA Negeri 2 Tambang. 2) To determine the quality ofmaterial the career prospects of various courses in colleges produced. This material was validated by the supervisor I, II lecturers, teachers, guidance and counseling, as well as 42 students of class XI IPA 3 SMAN 2 Mine. This material was tested to the student with the allocation of time of 4 hours of lessons (4 x 45 '). This material consists of a definition of career prospects, aspects of career maturity, career planning, career planning measures, Career Pathways, and the types of courses in college and career prospects. The results of the development of this material indicates the quality of thematerial produced is in the category of "Very Good", with the acquisition of a score of 4.3 for the entire aspect of the assessment.Keywords : Improving of guidance materials counseling , career prospects science, engineeringand natural sciences